Efficacy and safety of intravitreal aflibercept therapy in diabetic macular edema - Ali Cihat Aslan (Medicine Science, 2019)
To conduct a retrospective evaluation of the efficacy and safety of intravitreal aflibercept treatment in diabetic macular edema. Patients treated with intravitreal aflibercept for diabetic macular edema participated in this study. Three injections were administered to the previously untreated 76 eyes of 50 patients for 3 consecutive months with one-month interval. The results were evaluated retrospectively by analyzing the patients medical records. The patients values of best corrected visual acuity inverted according to Snellen chart, and their central macular thickness and intraocular pressure were compared before and after treatment. The average age of the patients was 57.2 ± 10.1. Of the cases, 77.6% were phakic, and 22.4% were pseudophakic. The increases in best corrected visual acuity in the first month after each injection and at the end of the third month were statistically significant (p < 0.001). The mean central macular thickness was 405.63 ± 106.93 μm before treatment and 288.83 ± 62.49 μm after the third injection. This reduction in the mean central macular thickness was statistically significant (p < 0.05). During and after the three-month follow-up of the injection application process, the most common observed ocular side effect was subconjunctival hemorrhage (34.2%). During or after the applications, no systemic side effects, such as sudden death, thromboembolic events, or myocardial infarction, were seen. Functionally and anatomically, intravitreal aflibercept injection therapy in diabetic macular edema is an effective treatment option because it improves visual acuity and decreases central macular thickness. [Med-Science 2019; 8(2.000): 412-7]